PENERAPAN SIG UNTUK PENYUSUNAN DAN ANALISIS LAHAN KRITIS PADA SATUAN WILAYAH PENGELOLAAN DAS AGAM KUANTAN, PROVINSI SUMATERA BARAT - Sutopo Purwo Nugroho (Jurnal Teknologi Lingkungan, 2008)
The increment of critical land extent is still undergoing because of change of land use without accompanied with conservation of land and water proportionally. Hence, it is need to carry out rehabilitation of land and forest by considering critical land map which is purposed to define priority scale, both its spatial and time. By applying technology of Geographic Information System (GIS), it can be mapped critical land according to standard of critical land criteria. In addition, the constraint of manual map can be reduced, particularly in information processing and map reproduction. In Agam Kuantan Watershed, critical land of forest has extent of 778.704,2 ha, and outside there area is about 496.486,7 ha.